Altruism as a pathway to unethical action. Issue 2 (5th February 2020) - Babula, Michael; Tookey, Max; Muschert, Glenn; Neal, Mark
Abstract : Purpose: The purpose of this paper is to answer the question, "Can particular types of altruism influence people to make unethical decisions?" The purpose of seeking to answer this question is to better understand those cases in personal, public and commercial life whereby a decision-maker is influenced by what is widely perceived to be a positive thing – altruism – to make unethical choices. Design/methodology/approach: An experiment was designed to test the influence of different categories of altruism on decision-making about whether to find another guilty for a regulatory transgression. This involved the establishment and running of a student panel at a UK university, which was given the task of determining the guilt or otherwise of two students accused of plagiarism – one from a poor background; one from a rich background. Through a survey of both the decision-makers and their judgments, and by analyzing the data using t -tests and Mann–Whitney tests, the associations between different categories of altruism and the decisions made could be ascertained. Findings: A total of 70.7% of the participants voted "not-guilty" for the poor student, whereas 68.3% voted "guilty" for the wealthy student. This indicated that self-interested, namely, egoistic altruism complemented by social and self-esteem needs gratification was significantly associated with violating foundational ethical principles. Originality/value: This is the first study to be done that attempts to evaluate the relationships between different categories of altruism and ethical decision-making. The findings here challenge aggregating all forms of empathy together when exploring the antecedents of unethical behavior.